Advanced compiler design and implementation - Muchnick, Steven S. (Morgan Kaufmann Publishers, 1997)
This comprehensive, up-to-date work examines advanced issues in the design and implementation of compilers for modern processors. Written for professionals and graduate students, the book guides readers in designing and implementing efficient structures for highly optimizing compilers for real-world languages. Covering advanced issues in fundamental areas of compiler design, this book discusses a wide array of possible code optimizations, determining the relative importance of optimizations, and selecting the most effective methods of implementation.